Robust chip-matched myriad filter-based multiuser receiver for impulsive channels - LIM, H; CHUAH, T; CHUAH, H (ELSEVIER SCIENCE BV, 2008)
The problem of impulsive noise suppression for direct-sequence code-division multiple-access (DS-CDMA) systems employing multiuser detection in impulsive channels is treated. Prior to the detector, linear chip-matched filter is commonly used for continuous-to-discrete-time conversion. The effects of the non-Gaussian impulsive channel in an asynchronous system are studied by modeling the samples of noise before front-end filtering as a symmetric alpha-stable process. The error probability performance of the linear correlation receiver under these conditions is compared to that for additive white Gaussian noise (AWGN) channels. It is found that the approach performs poorly in the presence of impulsive noise. To overcome this problem, an impulse mitigation strategy derived from the myriad filtering framework is employed to produce reliable soft channel outputs over a wide range of noise characteristics. The asymptotic error probability performance of the chip-matched myriad filter (CMMyF)-based receivers is then computed and compared to the computer simulated expression. The results show that, in contrast to the linear filter, the CMMyF is effective in removing the impulsive noise and leads to a reliable recovery of the desired chips with low estimation error. The proposed method proves to be fruitful in that the subsequent k-opt multiuser detector is safe to process the chip samples obtained hereafter, thereby retaining all its optimality and advantages. (C) 2007 Elsevier B.V. All rights reserved.